2019
DOI: 10.1021/acs.jmedchem.9b00191
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lysine-Based Thioureas as Mechanism-Based Inhibitors of Sirtuin 2 (SIRT2) with Anticancer Activity in a Colorectal Cancer Murine Model

Abstract: Sirtuin 2 (SIRT2) is a protein lysine deacylase that has been indicated as a therapeutic target for cancer. To further establish the role of SIRT2 in cancers, it is necessary to develop selective and potent inhibitors. Here, we report the facile synthesis of novel lysine derived thioureas as mechanism-based SIRT2 inhibitors with anticancer activity. Compounds AF8, AF10, and AF12 selectively inhibited SIRT2 with IC 50 values of 0.06, 0.15, and 0.08 μM, respectively. Compounds AF8 and AF10 demonstrated broad cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Reintroduction of a short-chain thioacetyl group (compounds S1-S4, Scheme S1, ESI †) led to significantly decreased potency against SIRT2, while displaying respectable inhibition against SIRT1, further emphasizing the importance of a longer chain acyl group to target SIRT2 over SIRT1 and SIRT3. 24,75 With compound 9 as the starting point, we then investigated the importance of the i + 1 residue. In some X-ray co-crystal structures of SIRT2, residues surrounding this position are unresolved due to high flexibility and unstructured binding interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Reintroduction of a short-chain thioacetyl group (compounds S1-S4, Scheme S1, ESI †) led to significantly decreased potency against SIRT2, while displaying respectable inhibition against SIRT1, further emphasizing the importance of a longer chain acyl group to target SIRT2 over SIRT1 and SIRT3. 24,75 With compound 9 as the starting point, we then investigated the importance of the i + 1 residue. In some X-ray co-crystal structures of SIRT2, residues surrounding this position are unresolved due to high flexibility and unstructured binding interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Reintroduction of a short-chain thioacetyl group (compounds S1-S4, Scheme S1) led to significantly decreased potency against SIRT2, while displaying respectable inhibition against SIRT1, further emphasizing the importance of a longer chain acyl group to target SIRT2 over SIRT1 and SIRT3. 24,75 With compound 9 as the starting point, we then investigated the importance of the i+1 residue. In some X-ray co-crystal structures of SIRT2, residues surrounding this position are unresolved due to high flexibility and unstructured binding interactions.…”
Section: Structure-activity Relationship Study and X-ray Crystallographymentioning
confidence: 99%
“…In contrast, Cheon et al reported that treatment of human colon cancer cells with the SIRT2-specific inhibitor, AK-1, which inactivates the NFκB/CSN2 pathway to induce proteasomal degradation of Snail, upregulated p21 to induce G1 arrest and delayed proliferation (65). Farooqi et al presented novel lysine-based thiourea compounds as potent and selective SIRT2 inhibitors that were less hydrophobic and easier to synthesize than TM (44), which potently inhibited tumor growth in an HCT116 xenograft murine model, supporting a role for SIRT2 as a viable therapeutic target for CRC (66) (Figure 1).…”
Section: Molecular Pathways Targeted By Sirt2mentioning
confidence: 99%